The Effect of HPMC and PVP Bases on the Formulation of Physical Properties and Transdermal Stability of Patch Estrak leaves of Jarak Pagar (Jatropha curcas L.) - Makkayu, Juand Valentino; Suwitono, Marvel Reuben; Sulastri, Titin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Open wounds are tissue damage that increases the risk of infection and requires proper treatment. Castor leaves (Jatropha curcas L.) contain flavonoids, saponins, and tannins, which have anti-inflammatory and antiseptic properties, aiding in tissue regeneration and infection prevention. To enhance its effectiveness, the extract is formulated into a transdermal patch, allowing direct drug absorption through the skin with stable release and convenient application. This study aims to determine the best formulation and optimal concentration of Hydroxypropyl Methylcellulose (HPMC) and Polyvinylpyrrolidone (PVP) in transdermal patches to improve stability and release effectiveness of the active compounds from castor leaf extract while evaluating their potential in accelerating wound healing. The transdermal patches were prepared using three variations of HPMC and PVP concentrations: F1 (HPMC 1 g : PVP 0.5 g), F2 (HPMC 0.75 g : PVP 0.75 g), and F3 (HPMC 0.5 g : PVP 1 g). Evaluations included organoleptic tests, pH, thickness, folding endurance, and moisture absorption. The results showed that F1 was the optimal formulation, exhibiting favorable physical characteristics and meeting the required standards, as it had the best mechanical properties with higher folding endurance, optimal thickness, and uniform weight distribution, ensuring better flexibility, durability, and stability. These findings indicate that variations in HPMC and PVP concentrations significantly affect the formulation and stability of transdermal patches, with F1 being the most effective formulation for potential wound healing applications.